A multidimensional analysis of the financial condition of rural communes in Poland in 2007–2011 - Bieniasz, Anna; Gołaś, Zbigniew; Łuczak, Aleksandra (Instytut Rozwoju Wsi i Rolnictwa Polskiej Akademii Nauk, 2014)
The main objective of this paper was to evaluate the financial condition of rural communes in Poland in the period 2007-2011. The study was based on financial ratios of the Finance Ministry and the data from the Local Data Bank CSO. Ratio Analysis and the Technique for Order Preference by Similarity to an Ideal Solution (TOPIS) was used for the evaluation the financial performance of rural communes. The value of the TOPSIS technique is that it allows for the isolation and shows the characteristics of four typological parameters. The financial condition of rural communes was additionally compared between that of urban and semi-urban areas.A logit regression method was used for the analysis of the determinants of the financial condition rural communes. The study showed, that an average synthetic measure of the financial condition did not differentiate significantly according to the types of communes, however, it did indicate a slight deterioration of the assessment in 2011 compared to 2007. Analysis of synthetic ratings budget relations, indicators per capita and debt allowed for the identification of specific characteristics of rural communes compared to other types of communes. They were characterized by having much lower, financial independence than in other types of communes, while working out a budget surplus, a higher level of current transfers per capita, a lower share of liabilities in total income and a lower burden of own income for debt service expenditure. Rural communes with the best and the worst financial conditions represented about 15% of communes. 34% and 32% Communes were in the low-and middle-level range of financial condition in 2011. Significant factors, under the parameters of the logit model which shaped every level of the financial condition, were: the ability to create income, spending and debt policy, sources of financing education, the size of the commune, the scale of unemployment and the migration process.
Keywords: financial condition; rural communes; TOPSIS; logit regression function